Pre-formulation investigations for establishing a protocol for treosulfan handling and activation. (28th May 2019) - El-Serafi, Ibrahim; Loy, Orlaith; Zhao, Ying; Oerther, Sandra; Mattsson, Jonas
Abstract: Introduction: Treosulfan is an alkylating agent that is used for the treatment of ovarian cancer and for conditioning prior to stem cell transplantation. It is a prodrug that is activated non-enzymatically to two active epoxides. Objectives: To optimize a protocol for both in vivo samples handling and in vitro drug preparation. Treosulfan stability was tested in biological fluids at different conditions as well as for its cytotoxicity on cell lines. Results: Plasma samples can be safely frozen for a short period up to 8 h, however; for longer periods, samples should be acidified. Urine samples and cell culture media can be safely frozen regardless their pH. For in vitro investigations, incubation of treosulfan at 37 °C for 24 h activated 100% of the drug. Whole blood acidification should be avoided for the risk of hemolysis. Finally; treosulfan cytotoxicity on HL-60 cells has increased following pre-incubation for 24 h at 37 °C compared to K562 cell line. Conclusion: The stability profiling of treosulfan provided a valuable reference for handling of biological samples for both in vivo and in vitro studies. These results can be utilized for further investigations concerning the drug kinetics and dynamics in addition to the development of new pharmaceutical formulations.